2022
DOI: 10.3389/fpubh.2022.768400
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Correlates of Non-suicidal Self-Injury Within a Sample of Adolescents With Mood Disorder

Abstract: BackgroundAccording to the integrated theoretical model, adolescents' behaviors were the outcome of the complex interplay between multiple levels. Non-suicidal self-injury (NSSI) is a serious and high prevalent problem among adolescents with mood disorders. However, a systematic perspective on psychosocial correlates among Chinese clinical adolescents is still rare.MethodThe impact of several factors at the individual (i.e., sex, age, self-esteem, and psychological distress), family (i.e., family structure, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
(90 reference statements)
2
3
0
Order By: Relevance
“…Consistent with the findings in the literature, we found in our clinical samples that NSSI is a common occurrence among those with mood disorders (41,42). We also found that NSSI was more frequently seen in female patients, in concordance with previous studies (43).…”
Section: The Key Features Of Nssi In Adolescent Patients With Mood Di...supporting
confidence: 93%
“…Consistent with the findings in the literature, we found in our clinical samples that NSSI is a common occurrence among those with mood disorders (41,42). We also found that NSSI was more frequently seen in female patients, in concordance with previous studies (43).…”
Section: The Key Features Of Nssi In Adolescent Patients With Mood Di...supporting
confidence: 93%
“…The findings of this study are also in accordance with the results of research by Buelens et al (2019) and Michl et al (2013), that the high level of psychological stress will be followed by an increase in rumination in response to stress experienced by individuals. In addition, this finding is also supported by Richmond et al (2017), Ganaprakasam et al (2021), Meng at al. (2022), which states that psychological stress is related to NSSI, the more stressed the individual, the higher the involvement in NSSI behavior.…”
Section: Difference Testsupporting
confidence: 77%
“…Individuals who respond to stress with rumination cause cognitive discomfort and make their negative mood increase and last longer than they should (Selby et al, 2013;Nagy et al 2022;Tonta et al, 2022). Then, the role of distress towards NSSI is supported by research results (Houben et al, 2017;Meng et al, 2022). In accordance with the emotional cascade model theory, the presence of high psychological distress will make individuals have negative feelings or intense unpleasant feelings, and NSSI exists as a distraction strategy to rapidly reduce the individual's intensive negative feelings, leading to relief and even increasing positive feelings, in this case adolescent victims of bullying.…”
Section: Difference Testmentioning
confidence: 88%
“…There are significant gender differences in NSSI among adolescents, with girls being more at risk than boys ( 40 , 41 ). NSSI is also associated with age ( 1 , 2 ).…”
Section: Methodsmentioning
confidence: 99%